STUDY OF DEMOTIVATED VS. MOTIVATED EFL LEARNERSâ€™ PREFERENCES TOWARDS TEACHERSâ€™ ORAL ERROR CORRECTION - Rezvan Jafari; Habibollah Mashhadi; Farideh Okati; Roya Movahed (University of Kuningan, 2017)
The purpose of this study is to compare the possible differences between demotivated vs. motivated EFL learnersâ€™ preferences toward teachersâ€™ oral error correction, including the necessity, frequency, timing, type, method, and delivering agent of error correction. To this end, 141 Iranian EFL learners at the departments of foreign language in Zabol and Sistan and Baluchestan universities participated in this study. The learnersâ€™ preferences for error correction questionnaire, the demotivation questionnaire, semi-structured interviews, and classroom observations were used to collect the data. The results of independent sample t-tests indicated that there were no significant differences between the two groups regardless of their demotivation level toward oral error correction. The findings revealed five suggestions: firstly, errors should be corrected and sometimes to be corrected.Â Secondly, correcting errors â€œafter the student finishes speakingâ€ was the most appropriate time among the two groups. Thirdly, â€œserious spoken errors that may cause problems in listenersâ€™ understandingâ€ and â€œfrequent errorsâ€ should be corrected more than other errors. Fourthly, â€œelicitationâ€ and â€œexplicit feedbackâ€ were the most popular methods of corrective feedback among the two groups. Finally, teachers were the most preferred person to deliver corrective feedback. Furthermore, the results of the observation data showed that what students received as error correction in oral classes were not in line with what students preferred to be corrected. Pedagogical implications for providing oral error correction have also been discussed.Keywords: oral corrective feedback, demotivated learners, motivated learners, preferences, EFL learners